Proceedings of the 7th Euro American Conference on Telematics and Information Systems 2014
DOI: 10.1145/2590651.2590674
|View full text |Cite
|
Sign up to set email alerts
|

An assistant agent for group formation in CSCL based on student learning styles

Abstract: In Computer Supported Collaborative Learning (CSCL) systems, students work in groups interacting by using computers. Each member of the team behaves in a particular way to collaborate with others, manifesting a particular learning style. In this paper we propose a new approach for automatically creating student groups in CSCL systems by considering their individual learning styles. Data mining techniques are applied to discover which existent combinations of learning styles lead to a better performance. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…Ahmad and Tasir [19] used log files of online learning activities to analyze the behavior patterns of engineering students; they concluded that the course structure, students' previous experience, and subject influence the thresholds defined for learning style identification. Costaguta and Menini [20] studied the relationship between learning style and performance to improve group creation. More recently, Shobbrook et al [21] implemented elements of EDM to validate the Fedler and Silverman's Index of Learning Styles (ILS) developed for engineering education.…”
Section: Learning Style Study Patterns and Study Profilementioning
confidence: 99%
“…Ahmad and Tasir [19] used log files of online learning activities to analyze the behavior patterns of engineering students; they concluded that the course structure, students' previous experience, and subject influence the thresholds defined for learning style identification. Costaguta and Menini [20] studied the relationship between learning style and performance to improve group creation. More recently, Shobbrook et al [21] implemented elements of EDM to validate the Fedler and Silverman's Index of Learning Styles (ILS) developed for engineering education.…”
Section: Learning Style Study Patterns and Study Profilementioning
confidence: 99%
“…Zheng and Pinkwart [27] used the discrete particle swarm optimization algorithm to heterogeneous group learners according to their personality traits and gender. Costaguta et al [28] and Lescano et al [29] present an approach to performing the automatic group formation of students in collaborative environments, which considers their learning styles, applying data mining techniques and genetic algorithms. Basu Roy et al [30] employed a semantics-based recommendation system for group formation with different objectives.…”
Section: About Group Formationmentioning
confidence: 99%
“…Em seguida, 34% dos trabalhos têm foco em otimização de algoritmos para formar os grupos [21,39,34,41,26,43,35,32,27,15]. Há também abordagens que buscam formar grupos com base no Estilo de Aprendizagem dos estudantes (11%) [20,31,17]. Outras contribuições dos trabalhos primários (7%) têm foco na implementação de sistemas baseados em Web [25,38] para formar grupos efetivos, utilizando, por exemplo, interface de usuário para configuração dos agrupamentos.…”
Section: Abordagens Para Formação De Grupos Encontradas Nos Trabalhosunclassified
“…Em seguida, tem-se 28% que considera o tipo de grupo heterogêneo e homogêneo por desempenho em atividade de colaboração, obtido pelo nível de interação entre os estudantes [25,38,42,23,19,40,30,27]. O tipo de grupo por estilo de aprendizagem pode ser encontrado em 10% dos trabalhos analisados [20,31,17]. O tipo de grupos mistos, que combinam os perfis de grupos anteriores, são encontrados em 14% dos trabalhos analisados [39,26,18,15].…”
Section: Tipos De Grupos Encontrados Nos Trabalhos Primáriosunclassified